PENUNJUKAN ANAK LUAR KAWIN SEBAGAI AHLI WARIS DENGAN TESTAMEN BAGI GOLONGAN TIONGHOA - AGNES ADRIANI HALIM (PREMISE LAW JURNAL, 2016)
There were some problems of appointing an illegitimate child as an heir : First, not all testaments contain the appointment of an heir for an illegitimate child; therefore, a Notary is needed in the process of drawing up the testament which is called a erfstelling testament. Secondly, in inhering an inheritance, an illegitimate child does not automatically inherit; it depends on the amount of share through testament (will) by his parents. Thirdly, there are some process which will be done in appointing an illegitimate child. The process of implementing a testament for an illegitimate child should fulfill the requirements of the testament, the completion of all documents, and inheritance certificate from his father (testator). Keywords : Illegitimate, Child, Testament